Excavating Intercultural Communication At Tourism Facilities Intentions To Visitor Satisfaction : Intercultural Communication, Tourism - Fitri, Wahyu Nurul; Syam, Ummi Khaerati; Sangkala, Ismail; Suleymanova, Nargiza (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2024)
This research was conducted at one of the tourist locations, namely Ke'te Kesu', North Toraja Regency. The aim of this research are to identify Information needs by the tourists in terms of intercultural communication and to identify the satisfaction of tourist. As well as, creating innovations to overcome these problems for tourist satisfaction. In the data collection process, this research uses the Design Thinking methodology stages. The four stages are (1) Sense and Sensibility, (2) Empathy, (3) Ideation and (4) Prototype. The research results show that there are difficulties in communicating due to language differences with local residents, so tourists sometimes experience confusion. Facilities at tourist locations lack safety because slippery stairs provide access for visitors to enjoy various destinations. Alternative solutions that have been provided by researchers include the Wonderful Toraja Application (WOTA) to make it easier for tourists to communicate and the Ke'te Kesu Tentacle (KeKel) to make it easier for tourists to access slippery stairs.